CHRISTOPHER SOUTHGATE'S COMPOUND THEODICY: PARALLEL SEARCHINGS: with Denis Edwards, "Christopher Southgate's Compound Theodicy: Parallel Searchings"; Ted Peters, "Extinction, Natural Evil, and the Cosmic Cross"; Robert John Russell, "Southgate's Compound Only‐Way Evolutionary Theodicy: Deep Appreciation and Further Directions"; Bethany Sollereder, "Exploring Old and New Paths in Theodicy"; Holmes Rolston, III, "Redeeming a Cruciform Nature"; Ernst M. Conradie, "On Social Evil and Natural Evil: In Conversation with Christopher Southgate"; Philip Clayton and Steven Knapp, "Evolution, Contingency, and Christology"; John F. Haught, "Faith and Compassion in an Unfinished Universe"; Celia Deane‐Drummond, "Perceiving Natural Evil through the Lens of Divine Glory? A Conversation with Christopher Southgate"; Nicola Hoggard Creegan, "Theodicy: A Response to Christopher Southgate"; and Neil Messer, "Evolution and Theodicy: How (Not) to Do Science and Theology.". Issue 3 (29th August 2018) - Edwards, Denis
Abstract: Christopher Southgate proposes that a theological response to the suffering that is built into an evolutionary world requires a compound evolutionary theodicy, made up of four interrelated theological positions. This article proposes a fourfold response to the suffering of nonhuman creation that parallels Southgate's compound theodicy. In its similarities and differences, it is offered in the spirit of a tribute to Christopher Southgate.